KEPUASAN PASIEN JAMINAN KESEHATAN MASYARAKAT (JAMKESMAS) BERDASARKAN DIMENSI KERAMAHAN DI PUSKESMAS PANTOLOAN KOTA PALU - I Kadek Wartana (Jurnal Ilmiah Kesmas -IJ, 2012)
Government efforts to help the poor and can not afford to provide health services through Community Health Insurance (JAMKESMAS). Through this Jamkesmas are expected for the poor in particular, can improve their health in order not to lag from other citizens who are better able to meet their needs for bealth. However, all that different from the reality in the field, a lot of poor people who can not get decent health care. The purpose of this research is the relationship between convivial dimension Knowledgeable health with a health card user satisfaction in Pantoloan Health Centers of Palu City.Kind of research is analytic study (cross-sectional). The variable in this study is convivial dimension (independent variable) and patient satisfaction (dependent variable). The data used are primary and secondary data Analysis is this research using univariate and bivariate analysis (chi-square test). The sample in this study amounted to 43 patients a health card. The sampling method by accidental sampling The results of the study showed that the chi-square test statistics obtained value of p=0.011 (p> 0.05) then Ho is rejected which means that there is a significant correlation between patient satisfaction with convivial dimension. Odds ratio of value to note that jamkesmas patients who the convivial dimension are bad have opportunities 7 times ( 95% CI 1.706 to 24.766) to less satisfied than patients who the convivial dimension are jamkesmas good. There was a significant association between convivial dimension to patient satisfaction. It is expected that the Pantoloan Health Center to further enhance the quality of service to patients, especially Jamkesmas patients through customer-oriented services by developing and manufacturing procedures generally friendly, time saving, and uncomplicated.